A Systematic Literature Review of Riba in Banking Industry - Mohamad fiqri pratama; Yaya Ruhenda Casmita Pujiharto; Aslam Nur Mei Widigdo; Fahmi Ali Hudaefi (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2026)
Purpose: This study aims to identify research trends, dominant themes, and existing research gaps related to riba in the banking industry, particularly in the context of Islamic finance development.Design/Methodology: This study employs a Systematic Literature Review (SLR) approach using a structured screening process. Articles were retrieved from Scopus and Google Scholar databases through Publish or Perish software. The review covers publications from 2014 to 2024, resulting in 98 eligible articles after applying predefined inclusion and exclusion criteria.Findings: The findings reveal that research on riba in the banking industry is primarily concentrated in three main areas: (1) Islamic legal interpretations of riba, (2) economic critiques of interest-based financial systems, and (3) institutional implementation of riba-free banking practices. However, significant gaps remain, including the limited integration between normative jurisprudential perspectives and empirical banking studies, as well as the lack of comparative analyses between Islamic and conventional financial systems.Practical Implications: The study highlights the need for a more integrative research approach that bridges Islamic legal theory and empirical financial practices. The findings can support academics, policymakers, and financial practitioners in developing more comprehensive, sustainable, and Sharia-compliant banking systems.Originality/Value: This study contributes to the literature by providing a structured synthesis of research on riba within the banking industry and identifying future research directions, particularly in advancing interdisciplinary and comparative studies in Islamic finance.